Parathyroid cancer: Outcome analysis of 16 patients treated at the princess margaret hospital. Issue 1 (31st January 2012) - Erovic, Boban M.; Goldstein, David P.; Kim, Dae; Mete, Ozgur; Brierley, James; Tsang, Richard; Freeman, Jeremy L.; Asa, Sylvia L.; Rotstein, Lorne; Irish, Jonathan C.
Abstract: Background: The purpose of this study was to discuss the appropriate management options for parathyroid carcinomas, which is still a subject of controversy. Methods: A retrospective chart review of 16 patients with parathyroid carcinoma was undertaken to determine the clinical outcome. Results: All patients were initially treated with surgery, and 11 patients received adjuvant radiotherapy. The 5‐ and 10‐year disease‐specific survival rates were 100% and 80%, respectively; the 5‐ and 10‐year disease‐free survival rates were 69% and 43%, respectively. The 5‐ and 10‐year locoregional control rates were 69% and 52%, respectively; the 5‐ and 10‐year distant control rates were 89% and 74%, respectively. In this cohort, none of the clinicopathologic parameters could be defined as a predictor. Conclusion: In patients with parathyroid carcinoma, definition of prognostic factors and the role of adjuvant radiation treatment has still to be elucidated. Nevertheless, angioinvasion and positive resection margins are critical factors regarding disease‐free survival in patients with parathyroid carcinomas. © 2012 Wiley Periodicals, Inc. Head Neck, 2013